Valuation of sitting and standing in metro trains using revealed preferences. (April 2016) - Tirachini, Alejandro; Sun, Lijun; Erath, Alexander; Chakirov, Artem
Abstract: The estimation of differences in the value of in-vehicle time sitting and standing is usually made with stated choice (SC) data, partly due to the lack of revealed preference data. In this paper, we use the observed behaviour of a subset of metro users in Singapore, who are willing to travel a longer time (into the opposite direction or backwards) to secure a seat for the actual trip in the direction towards their destination. We use smart card transactions to estimate the share of users who are willing to travel in the opposite direction during the first part of their trip and the average train occupancy per section to estimate differences in the valuation of travel time sitting and standing – translated into a standing multiplier or standing premium, which is analogous to the crowding multiplier that is usually found in the crowding valuation literature. We find that the standing multiplier is between 1.18 and 1.24 with the current crowding levels in the morning peak and can be as much as 1.55 with a density of 3 standing passengers per square metre. The results are compared to previous SC studies from other countries. The values found here are an indication of a standing premium that can be used to assess the social benefit of increasing the seat capacity of a public transport system and of applying peak spreading strategies. Highlights: The disutility of standing and crowding is estimated in Singapore MRT system. A standing multiplier (SM) on the value of time is estimated. The SM increases with the level of occupancy in metro trains. The SM can be used to estimate benefits of increasing seat capacity.